If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -8(x + 6) = 2x + -56 Reorder the terms: -8(6 + x) = 2x + -56 (6 * -8 + x * -8) = 2x + -56 (-48 + -8x) = 2x + -56 Reorder the terms: -48 + -8x = -56 + 2x Solving -48 + -8x = -56 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -48 + -8x + -2x = -56 + 2x + -2x Combine like terms: -8x + -2x = -10x -48 + -10x = -56 + 2x + -2x Combine like terms: 2x + -2x = 0 -48 + -10x = -56 + 0 -48 + -10x = -56 Add '48' to each side of the equation. -48 + 48 + -10x = -56 + 48 Combine like terms: -48 + 48 = 0 0 + -10x = -56 + 48 -10x = -56 + 48 Combine like terms: -56 + 48 = -8 -10x = -8 Divide each side by '-10'. x = 0.8 Simplifying x = 0.8
| -50x-57x=-3(-72x-56)-19(58+17x) | | n/115-n=11/12 | | -4+3(1-3x)=3(-7+6x)-7 | | x^5-0.16x^3=0 | | -8x-5+3x=77+4x-9 | | (2x+5)(3x-2)(x-5)=0 | | -96(x-37)=32(1-58x) | | (2x+5)(3x-2)(x-5)= | | -17(94r+37)+57r=-82(20r-37) | | 8x-125=0 | | -8x-8=36-2x+4 | | 95-7x=38x+20 | | -5(20v-68)=90(v-30) | | 11(-11v+5)=6(1-12v) | | 2x+3=8x+1 | | 4x-6(7-x)=6 | | -6(x+3)-10=21+5 | | 38(63x+56)=32(76x+19) | | 4x+20=44-2x | | 4(x+1)=12+8x | | 11+0.16=20 | | 12-8x=93-29x | | -2x-32(1+9x)=-32(1-25x) | | M*20=340 | | -6(1-5n)=-6-8n | | x/28=1/4 | | y=34x | | 4(x-2)=3(x+9) | | 3(x+3)=2(x-17) | | x-3=4x-5 | | 2*x^2+60x+800=0 | | 10(x-1)+3(x+5)=44 |